EFEKTIVITAS VESSEL TRAFFIC SERVICE (VTS) BATAM TERHADAP KEAMANAN MARITIM INDONESIA - Muhammad Ade Naufal; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The Strait of Malacca is one of the most important straits in the world. Because the Strait of Malacca is an international trade route through which ships from various countries pass. For this reason, countries around the Strait of Malacca work hand in hand in maintaining security. One of them is the construction of a Vessel Traffic Service (VTS) to become one of the guardians of the Malacca Strait. This study discusses how effective the VTS is as an instrument of security guard against crimes that occurred in the Malacca Strait.This research applies security theory with the concept of maritime security and qualitative methods supported by the Realism Perspective and the nation-state as the level of analysis. With the existence of VTS, shipping security in the Malacca Strait will be safer and more secure. The safety of ships using the Strait of Malacca is guaranteed. The results of guarding the Malacca Strait will be brought to the Tripartite Technical Expert Group (TTEG) forum. Based on data from the International Chamber of Commerce (ICC) and the International Maritime Bureau (IMB), crimes that occurred in the Strait of Malacca have decreased significantly. In 2016-2019 there were no crimes recorded in the Strait of Malacca. VTS Batam recorded only 1 incident during the 2014-2019 period, the KM Orkim Harmony piracy incident.Keywords : VTS, TTEG, Malacca Strait.